What Impact Does the Uptake of Climate-Smart Agricultural Practices have on Rural Household Income? Evidence from Nigeria - Abdulrazaq Daudu; Latifat Olatinwo; Oyedola Kareem; Habeeb Yusuf; Olashile Adeyemi (Al-Qadisiyah Journal For Agriculture Sciences, 2023)
Recent studies have verified the importance of adopting CSA practices to reduce greenhouse gases (GHGs), combat climate change, and boost food security and farmers welfare. However, there have been few studies that have examined the causal impact of CSA practices on household income. This paper assesses the impact of adoption of CSA practices on farming households’ income in Northern Nigeria. Our sample consists of cross-sectional data of 480 (160 adopters and 320 non-adopters of CSA) rural farming households selected using randomize control trial (RCT) from three Northern States in Nigeria. This study employed propensity score matching (PSM) to establish the causal effect of adoption of CSA on households’ income while inverse probability-weighted regression adjustment (IPWRA) was used to controlled for selection bias that may arise from both observed and unobserved factors. We found that, age, education, farm size, access to extension, membership of association, and access to climatic information are positive and statistically significant influencing adoption of CSA practices among farming households. The empirical findings revealed that adoption significantly impacts the farming households’ income across the two estimators used. This highlights the importance of promoting adoption of CSA practices among rural farming households. Our findings emphasize that enlightenment campaign on CSA practices, access to extension and climate information, education of farming households, the size of farmland cultivated and group formation should be promoted in order to scale up its adoption and increase households’ income.